Submarine pipeline routing and inspection with geographical information system technology - Chai, Beng Chung (2006)
Major advances have been achieved in recent years in submarine pipeline routing and inspection. Various tools and techniques are used to ensure the maximum safety of the submarine pipelines. The resulting consequence of these tools and techniques is the ever increasing data volumes, with the management and subsequent analysis of the data becoming more and more of an issue. The objective of this study is to implement the capabilities of Geographical Information System (GIS) to assemble various submarine pipeline related datasets into a common, compelling, efficient, user-friendly and interesting visualization system. In this study, GIS is used as the Spatial Decision Support System (SDSS), to provide appropriate information for efficient decision-making in submarine pipeline routing and inspection activities. A review of the literature concerning submarine pipeline routing and inspection technologies as well as GIS applications for both operations has been made for a better understanding to the existing problem faced by the industry. With the proper conceptual, logical and physical model design, an integration system has been developed to assemble, manipulate and analyze various submarine pipeline related datasets into a geodatabase. Sequentially, numerous Least Cost Paths (LCPs) have been determined to identify the most preferred route from SpringField platform to AutumnField platform, while considering the myriad of complex spatial interactions according to the diversified routing criteria. The best routing is then prudently analysed based on these LCPs with several geoprocessing analysis. Meanwhile, this study has integrated Digital Video System (DVS) datasets into ArcGIS-ArcMap environment to simultaneously record multiple channels of inspection video into a geodatabase and replay them synchronously according to its geographic features. Finally, some recommendations for future studies are made to enhance the quality of this study as well as to minimize the risk of offshore industries